Electronic Pop-Up Books: Integrating Jambi Culture Icons to Contextualize Numerical Concepts In Early Childhood Islamic Education - Yusria Yusria; Elis Muslimah Nuraida; Diah Dwi Santri; Riri Marini (Journal of Childhood Development, 2026)
This research aims to develop an innovative Electronic Pop-Up Book for Early Childhood Islamic Education students, focusing on contextualizing abstract mathematical numbers through Jambi cultural icons. This research method Using a Research and Development (R&D) approach with a Development Studies design, the media underwent rigorous validation by material and media experts, followed by practicality and effectiveness trials involving 21 students. The results categorized the media as "Very Valid" with an average expert score of 91.25%, highlighting its seamless integration of cultural heritage and interactive digital features. Practicality tests showed high student engagement and ease of navigation, while the visual representation of Jambi icons made numerical concepts easier to grasp. Statistical analysis confirmed a significant increase in learning outcomes, proving the Electronik Pop-Up book effectively facilitates a deeper understanding of mathematical fundamentals. In conclusion, this media is a valid, practical, and effective pedagogical tool. By integrating local culture, it enhances mathematical literacy and fosters cultural appreciation, serving as a meaningful, engaging resource for early childhood educators.